What does it mean to be a convert? - Seise, Claudia (Azizah) (IslamiCity, 2019)
Coming to Islam is something really special. It is a big step. A new phase of life is starting. It means a lot of change and challenges. But converting to Islam also means to find peace, tranquility, love. It means to finally arrive, to have found what you were looking for since a long time. However, converting to Islam is not the end of this process. Coming to Islam is not the final goal of your search.